Antibacterial and deodorant cat litter and preparation method thereof
By using polymer material spraying process in cat litter to form a waterproof layer and heat and destroy it, the problem of degradation of gas-phase purification materials in cat litter is solved, and efficient antibacterial and deodorizing effects are achieved, which is suitable for the industrial production of cat litter.
Patent Information
- Application Number
- CN202411098019.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-12
AI Technical Summary
Existing cat litter products are difficult to meet the needs of antibacterial and deodorizing functions, especially the problem of significant decline in performance of gas-phase purification materials when secondary contact with water.
A waterproof layer is formed on the surface of the particles of the gas-phase purification material by polymer material spraying technology, and the inner and outer layers are connected through low-temperature drying and high-temperature heating to form antibacterial and deodorizing cat litter.
It significantly improves the antibacterial and deodorizing properties of cat litter, with a bactericidal rate of Staphylococcus aureus and E. coli as high as 99.99%, and a removal rate of ammonia and hydrogen sulfide as high as more than 90%. It has a simple process and low cost.
Smart Images

Figure CN119111402A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cat litter preparation and relates to antibacterial and deodorizing cat litter and a preparation method thereof. Background Art
[0002] Cat litter is a hygroscopic material specially designed for cat excretion, aiming to provide a dry and easy-to-clean environment. Early cat litters were mainly non-condensing cat litters, such as sawdust, pulp particles, silica gel, etc., which simulated sand and provided water absorption, making it easy to collect cat feces. With the continuous advancement of cat litter technology, people are not limited to such simple collection. Bentonite cat litter, tofu cat litter and mixed cat litter have come out one after another. Bentonite cat litter has good water absorption. It can completely absorb the water and urine in the feces, and then condense into a large hard ball, which is convenient and hygienic when cleaning. The disadvantage of bentonite cat litter is that it has a lot of dust. After a long time, a layer of white powder will cover the furniture. Some cats will cough and sneeze after smelling it. Tofu cat litter uses bean dregs as raw materials. After extrusion molding, there is no dust on the surface. After soaking in water, it becomes a paste and can be directly poured into the toilet and flushed away. With the rise in the price of soy products, the price of bean dregs raw materials has also risen, resulting in the price of tofu cat litter being much higher than that of bentonite cat litter. Mixed cat litter is a type of cat litter made by mixing bentonite cat litter and tofu cat litter in proportion. This type of cat litter combines the advantages of bentonite cat litter and tofu cat litter, while improving their disadvantages, becoming the mainstream product in the cat litter market.
[0003] With the continuous improvement of people's living standards, new requirements have been put forward for cat litter products, which not only require cat litter to absorb water and clump, but also require cat litter to have antibacterial and deodorizing functions. However, the products currently on the market are still difficult to meet people's needs. Summary of the invention
[0004] In order to overcome the defects of the prior art, the present invention provides a deodorizing cat litter and a preparation method thereof.
[0005] Gas-phase purification material is an air purification material used to adsorb and decompose gaseous pollutants in the air. Gas-phase purification materials can not only adsorb and decompose VOCs such as formaldehyde, toluene, and xylene in the air, but also efficiently remove odorous gas molecules such as ammonia, hydrogen sulfide, and skatole. Combining gas-phase purification materials with cat litter can effectively improve the antibacterial and deodorizing properties of cat litter. However, when rolling the outer layer of powder (soy dregs powder and bentonite powder), the sprayed aqueous solution enters the gas-phase purification material particles. Since the active ingredient permanganate of the gas-phase purification material is easily soluble in water, the gas-phase purification material will cause the permanganate to dissolve when it contacts water for the second time, resulting in a significant decrease in the deodorizing performance of the gas-phase purification material.
[0006] In order to solve the problem that the performance of gas-phase purification materials is significantly reduced due to contact with water during secondary processing, the present invention adopts a polymer material spraying process to form a waterproof layer on the surface of the gas-phase purification material particles, and then rolls the powder to adhere to its outer layer. After low-temperature drying, the outer layer (soy dregs and bentonite) reaches the specified moisture content, and then high-temperature heating is used to destroy the polymer waterproof layer, so that the inner and outer layers are connected, which can achieve water absorption and agglomeration, and can also absorb and decompose the odor in cat excrement, effectively improving the odor problem caused by cats going to the toilet.
[0007] The detailed technical scheme of the present invention is as follows:
[0008] A method for preparing antibacterial and deodorizing cat litter comprises the following steps:
[0009] (1) spraying a high-temperature-resistant polymer waterproof layer on the surface of a gas-phase purification material to obtain a gas-phase purification material with a polymer waterproof layer; the gas-phase purification material is an active particle loaded with permanganate, and the water content is 5-20 wt%;
[0010] (2) spraying a wetting agent on the surface of the gas phase purification material with a polymer waterproof layer, then adding powder, stirring so that the powder sticks to the surface of the gas phase purification material, repeatedly spraying the wetting agent and adding powder, until obtaining cat litter particles of appropriate size;
[0011] (3) The cat litter particles are first cryogenically dried to reduce the moisture content of the outer layer to below 20wt%, and then subjected to high temperature heating to destroy the polymer waterproof layer to obtain an antibacterial and deodorizing cat litter.
[0012] Preferably, the polymer waterproof layer is polytert-butyl acrylate and has a thickness of 50-150 μm.
[0013] Preferably, the molecular weight of the polytert-butyl acrylate is 30±10K.
[0014] Preferably, in step (1), the gas-phase purification material is placed in a sugar coating machine, the speed of the sugar coating machine is set to 20±5 rpm, polytert-butyl acrylate is heated to melt, and it is sprayed on the gas-phase purification material rolling in the sugar coating machine using a spray gun, and the spraying time is 20-60 s to obtain a gas-phase purification material with a polymer waterproof layer on the surface.
[0015] Preferably, the wetting agent is an aqueous solution of hyperbranched polylysine and succinic acid.
[0016] Preferably, the wetting agent is a hyperbranched polylysine and succinic acid in a mass ratio of 5-15:1, prepared into an aqueous solution with a concentration of 1-10 wt%.
[0017] Preferably, the moisture content of the outer layer of the cat litter particles in step (3) is 10±5wt%, and then the particles are heated with air blast at 150±10°C for 10±5min.
[0018] Preferably, the gas phase purification material in step (1) uses activated alumina balls as carriers, has an average particle size of 1.5±0.5 mm, and the permanganate is one or both of potassium permanganate and sodium permanganate; the powder in step (2) is one or both of bean dregs powder and bentonite; and the particle size of the cat litter particles is 2-3 mm.
[0019] Preferably, the gas phase purification material is prepared by first dissolving permanganate in water to prepare an aqueous solution with a concentration of 10-20wt%, then immersing activated alumina balls in the aqueous solution, and after the activated alumina balls are saturated with adsorption, they are removed and drained, and finally dried to a moisture content of 5-20wt%, preferably 10±5wt%.
[0020] The thickness of the polymer waterproof layer of the present invention will greatly affect the deodorizing effect of the cat litter. If the thickness of the waterproof layer is too small, it will not play a waterproof role. When rolling the outer layer of powder, the sprayed aqueous solution will enter the gas phase purification material particles, destroying the gas phase purification material and causing its deodorizing performance to decrease. If the thickness of the waterproof layer is too large, although it can protect the gas phase purification material particles from being destroyed when rolling the outer layer of bean dregs and bentonite, when the waterproof layer is destroyed by high temperature later, the pores formed after heating and removing the butene will be blocked due to the softening and flow of the polymer, and the waterproof layer cannot be completely destroyed. The gas phase purification material cannot play a role, resulting in a serious decrease in its deodorizing effect.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention combines gas phase purification materials with cat litter, which can effectively improve the antibacterial and deodorizing properties of cat litter. The 1-hour contact sterilization rate for Staphylococcus aureus and Escherichia coli is as high as over 99.99%, and the removal rate for odors such as ammonia and hydrogen sulfide is as high as over 90%.
[0023] (2) The preparation process of the present invention is simple, low in cost, and is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a photograph of cat litter particles of the present invention.
[0025] Figure 2 This is a diagram of the core-shell structure of cat litter particles.
[0026] Figure 3 The graph shows the antibacterial effect of the control sample (a) and the test sample (b) of Example 1 on Staphylococcus aureus after being cultured at 36°C±1°C for 48 hours.
[0027] Figure 4 The graph shows the antibacterial effect of the control sample (a) and the test sample (b) of Example 1 on Escherichia coli after being cultured at 36°C±1°C for 48 hours. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0029] 1. Calculation of time for spraying polymer waterproof layer:
[0030] Average volume of a single gas phase purification material particle:
[0031] R 球 -The average radius of gas phase purification material particles is 0.75mm.
[0032] Gas phase purification material density:
[0033] V g -Gas phase purification material particle pore volume, 0.60cc / g;
[0034] V Al -Alumina unit mass volume, 0.29cc / g.
[0035] Average mass of a single gas phase purification material particle: m 球单 =ρ 球 ×V 球单
[0036] Average volume of polymer waterproof layer sprayed on a single gas phase purification material:
[0037] d 膜 -Thickness of polymer waterproof layer.
[0038] Total volume of 1000g gas phase purification material particles sprayed with polymer material:
[0039] V 喷 - Atomizing nozzle flow rate, 10cc / s;
[0040] t 喷 -Spraying time of polymer waterproof layer: 20-60s.
[0041] Substituting the data into the above formula, it is calculated that the thickness of the sprayed polymer waterproof layer is about 50-150μm.
[0042] 2. Preparation of gas phase purification materials:
[0043] The gas phase purification material is made of activated alumina balls as carriers and loaded with permanganate as the active ingredient. The conventional preparation process of gas phase purification materials includes three process steps: liquid preparation, loading, and drying. First, permanganate is dissolved in water to make a 15wt% aqueous solution, and then the activated alumina balls are immersed in the aqueous solution. After the activated alumina balls are saturated with adsorption, they are removed and drained, and finally dried to a water content of about 10wt%.
[0044] Example 1
[0045] 1000g of gas-phase purification material with an average particle size of 1.5mm was placed in a sugar coating machine, and the speed of the sugar coating machine was set to 20rpm. Polytert-butyl acrylate with a molecular weight of 30K was heated to 100°C to melt it, and sprayed on the rolling gas-phase purification material in the sugar coating machine with a spray gun for 40s to obtain a gas-phase purification material with a polymer waterproof layer on the surface.
[0046] Take 80-100 mesh bean curd powder and bentonite powder, mix them evenly in a mass ratio of 5:5 to obtain 10 kg of mixed powder. Add hyperbranched polylysine and succinic acid in a mass ratio of 10:1 into water to prepare a 5wt% aqueous solution, i.e., a wetting agent.
[0047] A gas-phase purification material sprayed with a polymer waterproof layer is placed in a sugar coating machine, a wetting agent is sprayed to wet the surface of the gas-phase purification material, and then a mixed powder of bean dregs and bentonite is added, and the mixed powder is rolled to make the mixed powder stick to the surface of the gas-phase purification material, and the wetting agent and the mixed powder are repeatedly sprayed until the particle size of the cat litter particles increases to 2-3 mm. The obtained cat litter particles are dried at 60° C. for 8 hours, the moisture content is reduced to 10wt%, and then heated at 150° C. for 10 minutes to prepare a cat litter with a core of the gas-phase purification material.
[0048] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.11 mg / m 3 Reduced to 0.19 mg / m 3 , the ammonia removal rate was 91.0%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, 500g of the above cat litter sample was placed in 1.5m 3 The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.11 mg / m 3 Reduced to 0.08 mg / m 3 , the hydrogen sulfide removal rate is 92.8%.
[0049] Referring to the method for determining the total number of molds in feed in GB / T 13092-2006, take 1000g of the above cat litter sample, crush it through a 0.45mm aperture sieve, and reduce it to 250g by quartering. Take 25g of the crushed sample, put it into a triangular bottle containing 225mL of sterile diluent, and shake it on an oscillator for 30 minutes, which is a 1:10 dilution. Pipette 10mL of the 1:10 dilution, inject it into a test tube with glass beads, and mix it on a micro mixer for 3 minutes to disperse the mold spores. Take 1mL of the dispersed dilution and make a 10-fold dilution. Repeat the 10-fold dilution to make 3 gradient dilutions, add 1mL of each to a sterile plate, add an appropriate amount of high-salt Czapek medium to each plate, and culture it at 25-28℃±1℃ for 1 week. The total number of mold counts is <10CFU / g. The T / IGIA 015-2023 group standard for mixed cat litter requires that the total number of mold in cat litter be less than 4000 CFU / g.
[0050] Referring to the method for determining the total number of bacteria in feed in GB / T 13092-2006, take 1000g of the above cat litter sample, crush it through a 0.45mm aperture sieve, and reduce it to 250g by quartering. Take 25g of the crushed sample, put it into a triangular flask containing 225mL of sterile diluent, and shake it on an oscillator for 30min, which is a 1:10 dilution. Pipette 1mL of the 1:10 dilution, inject it into a test tube containing 9mL of dilution, and shake it for 30s to make a 1:100 dilution. According to the above operation method, make 10-fold incremental dilutions to make 3 gradient dilutions, add 1mL of each to a sterile plate, add an appropriate amount of agar culture medium to each plate, and culture it at 30℃±1℃ for 72h±3h. The total number of bacteria is <90CFU / g. T / IGIA015-2023 mixed cat litter group standard requires that the total number of bacteria in cat litter is <200000CFU / g.
[0051] The antibacterial effect of the above cat litter was evaluated with reference to the antibacterial and antibacterial effect evaluation method of WS / T 650-2019. Take the 24h fresh slant culture of the test bacteria (Staphylococcus aureus, Escherichia coli) and wash it with PBS, then dilute it to 5×10 6 CFU / mL~5×10 7CFU / mL, and prepare a bacterial suspension for use. Take 10g of the above cat litter sample, use a mortar to grind the particles into powder, pour it into a sterile bottle containing 100mL PBS, shake for 30min, take the supernatant and filter it to make an antibacterial agent for use. Take a sterile test tube, first add 5.0mL of antibacterial agent, place it in a 20℃±1℃ water bath for 5min, then add 0.1mL of test bacterial suspension, mix quickly and start timing immediately. After 1h of interaction, take 0.5mL of the test bacteria and antibacterial agent mixture and add it to 4.5mL of neutralizer and mix. After each tube of test bacteria and antibacterial agent mixture is acted on by the neutralizer for 10min, take 1.0mL of sample solution respectively, and determine the number of surviving bacteria according to the live bacteria culture counting method, and inoculate 2 plates for each tube of sample solution. When the number of colonies growing on the plate is large, use PBS for 10-fold serial dilution, and then count the live bacteria culture. At the same time, use PBS instead of antibacterial agent to conduct parallel experiments as a positive control. All test samples and control samples were cultured at 36°C ± 1°C for 48 hours and the final results were observed. Figure 3 and Figure 4 . Experimental results: The sterilization rate of Staphylococcus aureus is greater than 99.99%, and the sterilization rate of Escherichia coli is greater than 99.99%.
[0052] Example 2
[0053] 1000g of gas-phase purification material with an average particle size of 1.5mm was placed in a sugar coating machine, and the speed of the sugar coating machine was set to 25rpm. Polytert-butyl acrylate with a molecular weight of 30K was heated to 100°C to melt it, and sprayed on the rolling gas-phase purification material in the sugar coating machine with a spray gun for 20s to obtain a gas-phase purification material with a polymer waterproof layer on the surface.
[0054] Take 80-100 mesh bean curd powder and bentonite powder, mix them evenly in a mass ratio of 3:7 to obtain 10 kg of mixed powder. Add hyperbranched polylysine and succinic acid in a mass ratio of 15:1 into water to prepare a 1 wt% aqueous solution, i.e., a wetting agent.
[0055] The gas phase purification material sprayed with a polymer waterproof layer is placed in a sugar coating machine, a wetting agent is sprayed to wet the surface of the gas phase purification material, and then bean dregs and bentonite mixed powder are added, and the mixed powder is rolled to make the mixed powder stick to the surface of the gas phase purification material, and the wetting agent and the mixed powder are repeatedly sprayed until the particle size of the cat litter particles increases to 2-3mm. The obtained cat litter particles are dried at 60°C for 6h, the moisture content is reduced to 15wt%, and then heated at 160°C for 5min to make cat litter with a gas phase purification material core.
[0056] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.02 mg / m 3 Reduced to 0.18 mg / m 3 , the ammonia removal rate was 91.1%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.14 mg / m 3 Reduced to 0.08 mg / m 3 , the hydrogen sulfide removal rate is 93.0%.
[0057] Example 3
[0058] 1000g of gas-phase purification material with an average particle size of 1.5mm was placed in a sugar coating machine, and the speed of the sugar coating machine was set to 15rpm. Polytert-butyl acrylate with a molecular weight of 30K was heated to 100°C to melt it, and sprayed on the rolling gas-phase purification material in the sugar coating machine with a spray gun for 60s to obtain a gas-phase purification material with a polymer waterproof layer on the surface.
[0059] Take 80-100 mesh bean curd powder and bentonite powder, mix them evenly in a mass ratio of 7:3 to obtain 10 kg of mixed powder. Add hyperbranched polylysine and succinic acid in a mass ratio of 5:1 into water to prepare a 10 wt% aqueous solution, i.e., a wetting agent.
[0060] Put the gas phase purification material sprayed with a polymer waterproof layer in a sugar coating machine, spray a wetting agent to wet the surface of the gas phase purification material, then add the bean dregs and bentonite mixed powder, roll the mixed powder to make the mixed powder stick to the surface of the gas phase purification material, repeat the spraying of the wetting agent and the addition of the mixed powder until the cat litter particle size increases to 2-3mm. The obtained cat litter particles are dried at 60°C for 12h, the moisture content is reduced to 5wt%, and then heated at 140°C for 15min to make a cat litter with a gas phase purification material core.
[0061] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.05 mg / m 3 Reduced to 0.19 mg / m 3 , the ammonia removal rate was 90.7%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.02 mg / m 3 Reduced to 0.09 mg / m 3 , the hydrogen sulfide removal rate is 91.2%.
[0062] Example 4
[0063] The difference between this embodiment and embodiment 1 is that the molecular weight of polytert-butyl acrylate is 20K. Experimental results: the ammonia removal rate is 90.2%, and the hydrogen sulfide removal rate is 91.1%.
[0064] Example 5
[0065] The difference between this embodiment and embodiment 1 is that the molecular weight of polytert-butyl acrylate is 40K. Experimental results: the ammonia removal rate is 90.4%, and the hydrogen sulfide removal rate is 90.8%.
[0066] Comparative Example 1 (no gas phase purification material added)
[0067] Take 80-100 mesh bean dregs powder and bentonite powder, mix them evenly according to the mass ratio of 5:5, and obtain 10kg mixed powder. Hyperbranched polylysine and succinic acid are added to water according to the mass ratio of 10:1 to prepare an aqueous solution (wetting agent) with a concentration of 5wt%. Add bean dregs and bentonite mixed powder in a sugar coating machine, spray the wetting agent while rolling, so that the mixed powder rolls into a ball in the sugar coating machine, repeat the spraying of the wetting agent and the addition of the mixed powder until the particle size of the cat litter particles grows to 2-3mm. The obtained cat litter particles are dried at 60°C for 8h, and the moisture content is reduced to 10wt%, and cat litter is prepared.
[0068] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.09 mg / m 3 Reduced to 1.78 mg / m 3 , the ammonia removal rate was 14.8%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.10 mg / m 3 Reduced to 0.89 mg / m 3 , the hydrogen sulfide removal rate is 19.1%. Comparative Example 2 (no polymer waterproof layer sprayed)
[0069] Take 80-100 mesh bean dregs powder and bentonite powder, mix them evenly according to the mass ratio of 5:5, and obtain 10kg mixed powder. Hyperbranched polylysine and succinic acid are added to water according to the mass ratio of 10:1 to make an aqueous solution (wetting agent) with a concentration of 5wt%. Put 1000g of gas phase purification material with an average particle size of 1.5mm in a sugar coating machine, spray the wetting agent, wet the surface of the gas phase purification material, then add bean dregs and bentonite mixed powder, roll so that the mixed powder sticks to the surface of the gas phase purification material, repeat spraying the wetting agent and adding the mixed powder until the cat litter particle size grows to 2-3mm. The obtained cat litter particles are dried at 60°C for 8h, and the moisture content is reduced to 10wt%, making a cat litter with a gas phase purification material kernel.
[0070] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.07 mg / m 3 Reduced to 1.22 mg / m 3 , the ammonia removal rate was 41.1%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.08 mg / m 3 Reduced to 0.65 mg / m 3 , the hydrogen sulfide removal rate was 39.8%. Comparative Example 3 (the polymer waterproof layer spraying time was too short)
[0071] 1000g of gas-phase purification material with an average particle size of 1.5mm is placed in a sugar coating machine, and the speed of the sugar coating machine is set to 20rpm. Polytert-butyl acrylate with a molecular weight of 30K is heated to 100°C to melt it, and is sprayed on the gas-phase purification material rolling in the sugar coating machine using a spray gun. The spraying time is 10s to obtain a gas-phase purification material with a polymer waterproof layer on the surface. Take 80-100 mesh bean dregs powder and bentonite powder, mix them evenly according to a mass ratio of 5:5, and obtain 10kg mixed powder. Hyperbranched polylysine and succinic acid are added to water according to a mass ratio of 10:1 to prepare an aqueous solution (wetting agent) with a concentration of 5wt%. Put the gas-phase purification material sprayed with a polymer waterproof layer in the sugar coating machine, spray the wetting agent, wet the surface of the gas-phase purification material, then add the bean dregs and bentonite mixed powder, roll so that the mixed powder sticks to the surface of the gas-phase purification material, repeat the spraying of the wetting agent and the addition of the mixed powder until the cat litter particle size grows to 2-3mm. The obtained cat litter particles were dried at 60° C. for 8 h to reduce the moisture content to 10 wt %, and then heated at 150° C. for 10 min to prepare cat litter with a gas phase purification material core.
[0072] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.06 mg / m 3 Reduced to 1.01 mg / m 3 , the ammonia removal rate was 51.0%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.07 mg / m 3 Reduced to 0.50 mg / m 3 , the hydrogen sulfide removal rate was 53.3%. Comparative Example 4 (Spraying time of polymer waterproof layer is too long)
[0073] 1000g of gas-phase purification material with an average particle size of 1.5mm is placed in a sugar coating machine, and the speed of the sugar coating machine is set to 20rpm. Polytert-butyl acrylate with a molecular weight of 30K is heated to 100°C to melt it, and is sprayed on the gas-phase purification material rolling in the sugar coating machine using a spray gun. The spraying time is 120s to obtain a gas-phase purification material with a polymer waterproof layer on the surface. Take 80-100 mesh bean dregs powder and bentonite powder, mix them evenly according to a mass ratio of 5:5, and obtain 10kg mixed powder. Hyperbranched polylysine and succinic acid are added to water according to a mass ratio of 10:1 to prepare an aqueous solution (wetting agent) with a concentration of 5wt%. Put the gas-phase purification material sprayed with a polymer waterproof layer in the sugar coating machine, spray the wetting agent, wet the surface of the gas-phase purification material, then add the bean dregs and bentonite mixed powder, roll so that the mixed powder sticks to the surface of the gas-phase purification material, repeat the spraying of the wetting agent and the addition of the mixed powder until the cat litter particle size grows to 2-3mm. The obtained cat litter particles were dried at 60° C. for 8 h to reduce the moisture content to 10 wt %, and then heated at 150° C. for 10 min to prepare cat litter with a gas phase purification material core.
[0074] According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m 3 The ammonia purification effect was tested in the test chamber. After 24 hours of static adsorption and decomposition, the ammonia concentration in the test chamber was reduced from 2.05 mg / m 3 Reduced to 1.88 mg / m 3 , the ammonia removal rate was 8.3%. According to QB / T 2761-2006 indoor air purification product purification effect determination method, take 500g of the above cat litter sample and put it into 1.5m3 The hydrogen sulfide purification effect test was carried out in the test chamber. After 24 hours of static adsorption and decomposition, the hydrogen sulfide concentration in the test chamber was reduced from 1.07 mg / m 3 Reduced to 0.95 mg / m 3 , the hydrogen sulfide removal rate is 11.2%.
[0075] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing antibacterial and deodorizing cat litter, It is characterized in that The steps include: (1) spraying a high-temperature-resistant polymer waterproof layer on the surface of a gas-phase purification material to obtain a gas-phase purification material with a polymer waterproof layer; the gas-phase purification material is an active particle loaded with permanganate, and the water content is 5-20 wt%; (2) spraying a wetting agent on the surface of the gas phase purification material with a polymer waterproof layer, then adding powder, stirring so that the powder sticks to the surface of the gas phase purification material, repeatedly spraying the wetting agent and adding powder, until obtaining cat litter particles of appropriate size; (3) The cat litter particles are first cryogenically dried to reduce the moisture content of the outer layer to below 20wt%, and then subjected to high temperature heating to destroy the polymer waterproof layer to obtain an antibacterial and deodorizing cat litter.
2. The preparation method according to claim 1, It is characterized in that The polymer waterproof layer is polytert-butyl acrylate and has a thickness of 50-150 μm.
3. The preparation method according to claim 2, It is characterized in that The molecular weight of the polytert-butyl acrylate is 30±10K.
4. The preparation method according to claim 1, It is characterized in that Step (1) placing the gas phase purification material in a sugar coating machine, setting the speed of the sugar coating machine to 20±5rpm, heating polytert-butyl acrylate to melt, and spraying it on the gas phase purification material rolling in the sugar coating machine with a spray gun, the spraying time is 20-60s, to obtain a gas phase purification material with a polymer waterproof layer on the surface.
5. The preparation method according to claim 1 or 2 or 3 or 4, It is characterized in that The wetting agent is an aqueous solution of hyperbranched polylysine and succinic acid.
6. The preparation method according to claim 5, It is characterized in that The wetting agent is a hyperbranched polylysine and succinic acid in a mass ratio of 5-15:1, prepared into an aqueous solution with a concentration of 1-10wt%.
7. The preparation method according to claim 1 or 2 or 3 or 4, It is characterized in that The moisture content of the outer layer of the cat litter particles in step (3) is 10±5wt%, and the particles are then heated with air blast at 150±10°C for 10±5min.
8. The preparation method according to claim 1 or 2 or 3 or 4, It is characterized in that The gas phase purification material in step (1) uses activated alumina balls as carriers, has an average particle size of 1.5±0.5 mm, and the permanganate is one or both of potassium permanganate and sodium permanganate; the powder in step (2) is one or both of bean dregs powder and bentonite; and the particle size of the cat litter particles is 2-3 mm.
9. The preparation method according to claim 1 or 2 or 3 or 4, It is characterized in that The preparation of the gas phase purification material is as follows: firstly, permanganate is dissolved in water to prepare an aqueous solution with a concentration of 10-20wt%, then activated alumina balls are immersed in the aqueous solution, after the activated alumina balls are saturated with adsorption, they are fished out and drained, and finally dried to a moisture content of 5-20wt%.
10. Antibacterial and deodorizing cat litter prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of reaction type deodorization cat litter
CN115399247A
Dust-free multi-effect adsorptive mixed cat litter and preparation method thereof
CN117084181A
Toilet sand for pet and toilet for pet
JP1995111841A
